Analisis Makna Konotatif dan Perubahan Makna Kata “Viral” dalam Berita Media Online - Eman Sulaeman (Metonimia: Jurnal Sastra dan Pendidikan Kesusastraan, 2023)
Abstract This study is motivated by the use of the word viral which is often used to attract the latest information in online news media. The problem discussed is the analysis of connotative meaning and changes in meaning towards the use of the word viral. The purpose of this study is to explain the connotative meaning and changes in meaning towards the use of the word viral in online media. The research method used is descriptive qualitative. Based on the results of the discussion, it was found that lexically, in terms of the meaning of the word viral, it has a negative connotation. Meanwhile, the change in meaning that occurred in the viral news headline was "Polli and Apriyani's success in the gold medal. The word viral success causes a change in meaning. Ameliorative is a type of change in the meaning of a word for the better. The meaning of the word viral previously had a bad meaning or low loss, until finally it changed for the better or higher because of the positive context of the word "success" Keywords: viral, online news media, connotative, change of meaning, ameliorative Abstrak Kajian ini dilatarbelakangi oleh penggunaan kata viral yang kerap digunakan dalam penyampaian informasi terkini dalam media berita online. Masalah yang dibahas adalah analisis makna konotatif dan perubahan makna terhadap penggunaan kata viral. Tujuan dari kajian ini adalah untuk menjelaskan makna konotatif dan perubahan makna terhadap penggunaan kata viral dalam media online Adapun metode penelitian yang digunakan adalah deskriptif kualitatif. Brdasarkan hasil pembahasan, ditemukan bahwa secara leksikal, ditinjau dari makna kata viral mempunyai makna berkonotasi negatif. Sedangkan perubahan makna yang terjadi pada judul berita viral dari “kesuksesan polli dan Apriyani dalam medali emas. Kata viral kesuksesan tersebut menimbulkan perubahan makna Amelioratif merupakan jenis perubahan makna dari sebuah kata menjadi lebih baik. Artinya sebelumnya makna viral kata mempunyai makna yang buruk atau nilainya rendah, hingga akhirnya berubah menjadi lebih baik nilainya atau lebih tinggi karena konteks positif dari kata “kesuksesan” Kata Kunci: viral, media berita online, konotatif, perubahan makna, amelioratif,